Risk Management Practices of Islamic and Conventional Banks of Pakistan: A Comparative Study - Bashir, Rubina; Azeez, A. A. (UUM Press, 2022)
This paper is the report of a study that has investigated the impact of the risk management process, including liquidity and operational risk, on the risk management practices of Islamic banks and conventional banks in Pakistan. The study compared the risk management practices of both types of banks. Data was collected through the 200 self- administered questionnaires distributed to senior managers and risk officials of both types of banks. The data was analyzed using basic descriptive statistics, One-way ANOVA and Multiple regression analysis. The empirical results showed that risk assessment and analysis, risk monitoring and liquidity risk analysis were the most influential determinants of the risk management practices of conventional banks, whereas risk identification, risk assessment and analysis, credit risk analysis, liquidity risk analysis and operational risk analysis had influenced the risk management practices of Islamic banks. Overall, Islamic banks were better in terms of understanding risk management, risk identification, risk assessment and analysis, risk monitoring and operational risk analysis, while conventional banks were ahead of Islamic banks in credit risk analysis, liquidity risk analysis, and risk management practices. In the context of the emerging economy of Pakistan, the study outcomes can be helpful for investors, potential and existing customers to make prudent investment decisions. Findings are also helpful for strategy managers and regulators in policy formulation, elevation, and implementation of risk management regulations.